Weaving the Future of Islamic Civilization 2.0: Prospects and Challenges Learning from the Rise and Decline of Islamic Civilization - Andi Darmawan Putra (Green Publisher Indonesia, 2026)
This paper outlines the history of the rise of Islamic civilization—what started it and what became the factors in its decline, especially in the field of science, which was overtaken by Western civilization in the modern era. Knowing the history of how Islamic civilization developed into a successful one, reaching a golden age compared to others, and studying the factors that caused its decline can provide lessons for Muslims to envision the future of Islamic civilization today and beyond. The author examines thoughts from key Islamic figures on how they formulated scientific development based on Islam, including perspectives from Western orientalists who view Islamic civilization as an important contribution to world civilization. The method employed is a comparative qualitative approach through literature review, drawing on the scientific thinking and research of various scholars discussing Islamic civilization and its relationship to rational thought and science.